Developing the knowledge-based human resources that support the implementation of the National Dual Training System (NDTS): evaluation of TVET teacher's competency at MARA Training Institutions - Ali, Mahazani (2015)
Development in the world of technical and vocational education and training (TVET) on an ongoing basis is a challenge to the profession of the TVET-teachers to maintain their performance. The ability of teachers to identify the competencies required by their profession is very critical to enable them to make improvements in teaching and learning. For a broader perspective the competency needs of the labour market have to be matched by those developed within the vocational learning processes. Consequently, this study has focused on developing and validating the new empirical based TVET-teacher competency profile and evaluating teacher’s competency. This study combines both quantitative and qualitative research methodology that was designed to answer all the research questions. The new empirical based competency profile development and TVET-teacher evaluation was based upon an instructional design model. In addition, a modified Delphi technique has also been adopted throughout the process. Initially, 98 elements of competencies were listed by expert panel and rated by TVET institutions as important. Then, analysis using manual and statistical procedure found that 112 elements of competencies have emerged from seventeen (17) clusters of competencies. Prior to that, using the preliminary TVET-teacher competency profile, the level of TVETteacher competencies was found to be Proficient and the finding of 112 elements of competencies with 17 clusters was finally used to develop the new empirical based competency profile for MARA TVET-teacher. Mean score analysis of teacher competencies found that there were gaps in teacher competencies between MARA institutions (IKM) and other TVET institutions, where MARA-teacher was significantly better than other TVET teacher. ANOVA and t-test analysis showed that there were significant differences between teacher competencies among all TVET institutions in Malaysia. On the other hand, the study showed that teacher’s age, grade and year of experience are not significant predictors for TVET-teacher competency. In the context of mastering the competency, the study also found that three competencies are classified as most difficult or challenging, twelve competencies are classified as should be improved, and eight competencies are classified as needed to be trained. Lastly, to make NDTS implementation a reality for MARA the new empirical based competency profile and the framework for career development and training pathway were established. This Framework would serve as a significant tool to develop the knowledge based human resources needed. This will ensure that TVET-teachers at MARA are trained to be knowledgeable, competent, and professional and become a pedagogical leader on an ongoing basis towards a world class TVET-education system.